1997
DOI: 10.1097/00006676-199701000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Sphincterotomy and Recurrence of Acute Pancreatitis in Gallstone Patients Considered Unfit for Surgery

Abstract: The aim of the present prospective study was to investigate whether endoscopic sphincterotomy may be useful in preventing recurrence of acute pancreatitis in patients with gallstones and a high anesthesiological risk of cholecystectomy. Twenty-six elderly patients with severe cardiopulmonary, hepatic, and renal diseases were considered. Endoscopic sphincterotomy was successful in 19 cases (group A: mean age, 78.4 years; range, 71-87) and failed in 7 patients (group B: mean age, 79.8 years; range 73-85). In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 5 publications
4
27
0
2
Order By: Relevance
“…Uomo et al [6] prospectively investigated the effect of ES on patients after a first attack of ABP who were considered unfit for surgery. In the ES group, the observed rate of recurrent ABP was 5% compared with 57% in the conservative group after a mean follow-up period of 30 and 23.8 months, respectively.…”
Section: Endoscopic Sphincterotomy Versus Conservative Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Uomo et al [6] prospectively investigated the effect of ES on patients after a first attack of ABP who were considered unfit for surgery. In the ES group, the observed rate of recurrent ABP was 5% compared with 57% in the conservative group after a mean follow-up period of 30 and 23.8 months, respectively.…”
Section: Endoscopic Sphincterotomy Versus Conservative Managementmentioning
confidence: 99%
“…Recently, observational studies point toward a reduction in recurrent ABP attacks and other gallstone complications when ES is performed for selected groups of patients [6][7][8][9][10]. Based on whether a patient has undergone ES, cholecystectomy, or both, the post-ABP-status of a patient can be classified into four categories: 1 (no ES and no cholecystectomy), 2 (no ES with cholecystectomy), 3 (ES without cholecystectomy), or 4 (ES with cholecystectomy).…”
mentioning
confidence: 99%
“…It is also important to emphasize that a substantial number of patients with 'idiopathic' pancreatitis might have small gallstones that were undetected by abdominal ultrasound or computed tomography [12] . However, a certain percentage of patients are unfit for cholecystectomy because advanced age and presence of comorbidity [13,14] .…”
Section: Therapeutic Approach To Acute Biliary Pancreatitismentioning
confidence: 99%
“…Even if cholecystectomy is the main therapeutic option in patients with gallstones, some authors have proposed the use of ursodeoxycholic acid in order to prevent further attacks of acute pancreatitis having a biliary origin [15,16] ; others have suggested that endoscopic sphincterotomy might be an option, especially in patients considered unfit for surgery [13,14,17] . In fact, it has been suggested that endoscopic sphincterotomy is the method of choice for treatment of lithiasis of the common bile duct, particularly in elderly patients or in patients at poor operative risk [18][19][20] .…”
Section: Therapeutic Options In Patients Unfit For Cholecystectomymentioning
confidence: 99%
See 1 more Smart Citation